1970
DOI: 10.1111/j.1744-7348.1970.tb04562.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the viability of fungal sclerotia

Abstract: SUMMARY Simple methods for producing, handling and testing the viability of sclerotia were used on five fungi, three of which produced sclerotia freely in sand‐maizemeal cultures; the other two did not, and were grown on agar. After air drying, which did not affect viability, sclerotia were buried in the field in bags of nylon fabric. After recovery from soil they were surface‐sterilized with calcium hypochlorite and plated on a medium containing chloramphenicol and streptomycin sulphate. Some fungi, particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1971
1971
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…), respectively. Previous reports on the survival of sclerotia have cited 15 months for B. tulipae (Coley-Smith & Javed, 1970;Coley-Smith & Cooke, 1971;Javed, 1977), and 5-9 months for B. cinerea (Thomas et al, 1983), but we have not found any prior reports on the survival characteristics of sclerotia from fungi resistant to fungicides. In addition, many previous studies on sclerotia] survival have involved just one or two isolates per species (Coley-Smith, 1960;Coley-Smith & Javed, 1970;Javed, 1977;Coley-Smith t-r fl/., 1979).…”
Section: Introductioncontrasting
confidence: 63%
“…), respectively. Previous reports on the survival of sclerotia have cited 15 months for B. tulipae (Coley-Smith & Javed, 1970;Coley-Smith & Cooke, 1971;Javed, 1977), and 5-9 months for B. cinerea (Thomas et al, 1983), but we have not found any prior reports on the survival characteristics of sclerotia from fungi resistant to fungicides. In addition, many previous studies on sclerotia] survival have involved just one or two isolates per species (Coley-Smith, 1960;Coley-Smith & Javed, 1970;Javed, 1977;Coley-Smith t-r fl/., 1979).…”
Section: Introductioncontrasting
confidence: 63%
“…The methods used were mainly those of Coley-Smith and Javed (1970). Sclerotia of R. tuliparum isolate J53 (Gladders and Coley-Smith, 1978) were scraped from four-week-old cultures on Oxoid malt extract agar (20°C in darkness), washed in running tap water and then placed, together with a small quantity of sand, in bags of nylon fabric (50 sclerotia per bag).…”
Section: Plate IV Materials and Methodsmentioning
confidence: 99%
“…At intervals of one to three years they were dug up and their contents examined. The viability of sclerotia was measured by surface-sterilising them in the filtrate from a suspension of calcium hypochlorite in water (40/100, w/v) and then placing them individually on spots of Oxoid malt extract agar containing 1000 /xg streptomycin sulphate and 250 /ag chloramphenicol per ml (Coley-Smith and Javed, 1970).…”
Section: Plate IV Materials and Methodsmentioning
confidence: 99%
“…Sclerotia of S. cepivorum. S. gladioli and 5. minor were produced in pure cultures in mixtures of maizemeal with sand (Coley- Smith & Javed. 1970) or of maizemeal with perlite (Esler & Coley-Smith.…”
Section: Production Of Sclerotiamentioning
confidence: 99%
“…Material from IM-fim (S. cepivorum) or 80-//m (S, gladioli) mesh sieves was washed into petri dishes from which the sclerotia were removed individually with fine forceps. The sclerotia recovered were then tested for viability by surface-sterilizing them for 3-5 min (S. cepivorum) or 1 min (S. gladioli) in hypochlorite (IOg/1 available chlorine), rinsing them briefly in sterile distilled water, crushing them with sterile forceps, and then placing them individually onto droplets of PDA or Oxoid malt extract agar (MEA) containing 100 //g/ml of chloramphenicol and streptomycin sulphate (Coley-Smith & Javed. 1970;Coley-Smith, 1985).…”
Section: Recovery Of Sclerotiamentioning
confidence: 99%